An analysis of vitamin D levels and the factors affecting vitamin D levels among the adult population attending a tertiary care hospital - A., Amitha T.; S., Lekshmi G.; Roy, Jyothi (International Journal of Research in Medical Sciences, 2022)
Background: The aim of the study was to determine the vitamin D levels and the factors affecting vitamin D levels among the adult population attending a tertiary care hospital. Methods: An observational cross-sectional study was conducted among 568 adult individuals attending various outpatient departments at Sree Gokulam Medical College and Research Centre, Venjaramoodu over a period of 3 months from 1st January to 30th March of 2021. 119 males and 449 females were recruited in the study. Only adult patients between the age of 18 to 70 were included in the study. Blood samples were collected randomly from patients attending different OPDs. Serum 25-hydroxyvitamin D (25(OH) D) level was measured using electrochemiluminescence immunoassay (ECLIA) in Roche Cobas e 411 fully automated analyzer. Results: Among the study population, 52.9% of males had Vitamin D deficiency and 70.8% of females had vitamin D deficiency with a p value 0.001. Based on age, the study population was subdivided into three groups-young, middle age and old age groups. 76.9% of the young age group had vitamin D deficiency. 57.2% of middle age group and 56.8% of old age group were Vitamin D deficient with a p value 0.0001. Conclusions: Age and gender are significantly related to Vitamin D levels. While individual’s occupation, BMI and their religion are less significant factors correlated to vitamin D levels in an individual.